2023
DOI: 10.1093/bjs/znad101.151
|View full text |Cite
|
Sign up to set email alerts
|

O151 A comparison of pathological TNM 7 with TNM 8 staging for pancreatic ductal adenocarcinoma and distal cholangiocarcinoma

Abstract: Background The 8th edition of the TNM (tumour, nodes and metastasis) staging system was introduced in 2016 to improve the prognostic prediction of pancreatic ductal adenocarcinoma (PDAC). However, its superiority over the previous edition remains uncertain. This study evaluated the prognostic impact of TNM 7 with TNM 8 staging in patients with PDAC and distal cholangiocarcinoma. Methods A retrospective cohort study was conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…This is evident when considering the research conducted by Chen et al (2016) [7], where the prognostic efficacy of the staging characteristics from the 8th edition of the AJCC cancer staging manual [21] was evaluated, finding a C-index of 0.585. Similarly, in a study conducted by Mohammad et al (2023) [22], the observed C-index was found to be 0.633.…”
Section: Survival Modelingmentioning
confidence: 75%
“…This is evident when considering the research conducted by Chen et al (2016) [7], where the prognostic efficacy of the staging characteristics from the 8th edition of the AJCC cancer staging manual [21] was evaluated, finding a C-index of 0.585. Similarly, in a study conducted by Mohammad et al (2023) [22], the observed C-index was found to be 0.633.…”
Section: Survival Modelingmentioning
confidence: 75%